2020
DOI: 10.3390/pathogens9110969
|View full text |Cite
|
Sign up to set email alerts
|

Physics Comes to the Aid of Medicine—Clinically-Relevant Microorganisms through the Eyes of Atomic Force Microscope

Abstract: Despite the hope that was raised with the implementation of antibiotics to the treatment of infections in medical practice, the initial enthusiasm has substantially faded due to increasing drug resistance in pathogenic microorganisms. Therefore, there is a need for novel analytical and diagnostic methods in order to extend our knowledge regarding the mode of action of the conventional and novel antimicrobial agents from a perspective of single microbial cells as well as their communities growing in infected si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 174 publications
(254 reference statements)
0
3
1
Order By: Relevance
“…These results are consistent with the literature [25], which reported significant variations in the calculation of the Young's modulus, despite using the same sample tested. The deviation of Young's modulus for Kaolin obtained in the present study is significant when compared with the reference literature [31,32]. It can be explained on the basis that rough surfaces and pores on kaolin particles can cause the indenter to interact unevenly, affecting the contact area.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…These results are consistent with the literature [25], which reported significant variations in the calculation of the Young's modulus, despite using the same sample tested. The deviation of Young's modulus for Kaolin obtained in the present study is significant when compared with the reference literature [31,32]. It can be explained on the basis that rough surfaces and pores on kaolin particles can cause the indenter to interact unevenly, affecting the contact area.…”
Section: Resultscontrasting
confidence: 51%
“…During indentation, the resulting forces may damage the cantilever and/or the sample or the tip [29][30][31]. Therefore, it is considered necessary to resort to the proposed method to avoid this problem.…”
Section: Methodsmentioning
confidence: 99%
“…14–16 Several other studies have examined biofilm-related factors by AFM, including pili, adhesins and polysaccharides. 15,17–25 Additionally, using a laser trap, Maier, O'Toole and colleagues demonstrated that the retraction force of TFP of P. aeruginosa could exert a force of ∼30 pN. 26 Finally, we examined the role of TFP in adhesion of P. aeruginosa to a hydrophobic surface, revealing that a TFP could generate strong adhesive forces in a time-dependent manner and that a single pili can sustain forces up to 250 pN.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, in eukaryotes intracellular organelles, such as mitochondria, which are responsible for energy generation, also show nanomotion ( 42 ). Detecting nanomotion using fluorescent labelled products or organelles ( 43 ) is an interesting way to further explore nanomotion causes which might lead to new insights into the root cause.…”
Section: Introductionmentioning
confidence: 99%